A new variant of urethral duplication- collateral urethral duplication with paraspadiac meatus: A case report - Prashant Mulawkar (Pediatric Urology Case Reports, 2018)
We report a case of isolated collateral urethral duplication with accessory urethra in paraspadiac location. Paraspadias is a congenital condition where the urethra opens on one side of penis. A fouryear male child had collateral urethral duplication. One urinary meatus was located at normal apical position, whereas the other meatus was located on left side in paraspadiac collateral location. There was no other congenital malformation. The duplicated urethra was excised. Five cases of isolated collateral urethral duplication have been reported so far. We report the sixth such case and the first case of collateral urethra in paraspadiac location.